Study of scintillation light collection, production and propagation in a 4 tonne dual-phase LArTPC. (3rd March 2021) - Aimard, B.; Aizawa, L.; Alt, C.; Asaadi, J.; Auger, M.; Aushev, V.; Autiero, D.; Balaceanu, A.; Balik, G.; Balleyguier, L.; Bechetoille, E.; Belver, D.; et al.
Abstract: The 3×1×1 m 3 demonstrator is a dual phase liquid argon time projection chamber that has recorded cosmic rays events in 2017 at CERN. The light signal in these detectors is crucial to provide precise timing capabilities. The performance of the photon detection system, composed of five PMTs, are discussed. The collected scintillation and electroluminescence light created by passing particles has been studied in various detector conditions. In particular, the scintillation light production and propagation processes have been analyzed and compared to simulations, improving the understanding of some liquid argon properties.